A convenç\~ao da Organizaç\~ao dos Estados Americanos para as pessoas com deficiência e as políticas federais brasileiras: Indicadores de monitoramento e aç\~oes do governo federal - Igor Ferraz da Fonseca; Francine De Souza Dias (Instituto de Pesquisa Econômica Aplicada (IPEA), 2020)
– This paper aims to analyze federal public policies and normative devices in light of the monitoring indicators of the Inter-American Convention for the Elimination of All Forms of Discrimination against Persons with Disabilities (CIADDIS/OAS), promulgated by the Organization of American States (OAS). This article is divided into three parts: i) historical references to the CIADDIS/OAS and the establishment of its Committee (CEDDIS/OAS); ii) reflections on the construction of its indicators and; iii) an qualitative analysis of national laws and policies and its relation with the indicators. Among the results obtained, we highlight, on the one hand, the alignment between the OAS indicators and the Brazilian federal normative devices and policies and, on the other hand, a mismatch between the existence of legal instruments and public services really achieved by the persons with disabilities.
Keywords: F53; I31; I38; 330; CIADDIS; OAS; indicators; public policies; persons with disabilities